The death of the ‘perfect’ woman: the social implications of Song Yunping in the reform themed novel River of Time (2009) - Wang, Qing; Lim, Choon Bee; Chin, Mooi San (HRMARS, 2024)
The character Song Yunping is beloved and commemorated in the tribute drama Like a Flowing River, celebrating the 40th anniversary of China's reform and opening-up. The gender dilemma and inequality she endures in the original online novel River of Time, as well as the patriarchal social ideology, are often overlooked. Her ‘perfect’ image is shaped by the aesthetic paradigm of patriarchal society, aligning with traditional ideals of women. Her tragedy lies in the paradox of being confined to the domestic sphere while shouldering excessive public labour without compensation or professional dignity. From the grand narrative, her role as a virtuous wife clashes with the modernity demanded by the reform period. Her death marks not only the end of traditional womanhood but also symbolizes the fading of a bygone era during China's transitional period from the beginning of reform and opening-up in 1978 to the pursuit of socialist modernization.